2015
DOI: 10.1530/erc-15-0152
|View full text |Cite
|
Sign up to set email alerts
|

Identification of occult tumors by whole-specimen mapping in solitary papillary thyroid carcinoma

Abstract: We undertook this study to estimate an accurate incidence and spread patterns of occult papillary thyroid carcinoma (PTC) in patients with a preoperative diagnosis of solitary PTC by using whole-specimen mapping of all specimens after a total thyroidectomy. Enrolled prospectively in this whole-thyroid mapping study are 82 consecutive patients who underwent a total thyroidectomy under a preoperative diagnosis of solitary PTC. All thyroidectomy specimens were serially sectioned in 2 mm thickness and whole-thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
2
9
0
8
Order By: Relevance
“…Feng et al demonstrated that tumor > 1 cm was an independent predictor of contralateral carcinoma ( 32 ). In contrast, Park et al suggested that the size of the primary tumor could not be a predictor for contralateral carcinoma ( 33 ). Meanwhile, in a study that followed 992 patients with benign thyroid nodules for 5 years, Durant et al reported an increase in diameter for at least 2 mm in 15.4% of the nodules ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al demonstrated that tumor > 1 cm was an independent predictor of contralateral carcinoma ( 32 ). In contrast, Park et al suggested that the size of the primary tumor could not be a predictor for contralateral carcinoma ( 33 ). Meanwhile, in a study that followed 992 patients with benign thyroid nodules for 5 years, Durant et al reported an increase in diameter for at least 2 mm in 15.4% of the nodules ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason is that region VI is a blind area for US [38]. Second, five patients in the surgical group had multifocal disease according to the final pathology, which showed small (1-2 mm) and occult (<2 mm) carcinomas that could easily be missed by US [39]. Thus, the conventional examinations (US, FNAC) could not evaluate a solitary tumor with great validity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2015 ATA guidelines, for tumors lesser than 4 cm, confined to one lobe, absent of extrathyroidal extension (ETE), and clinical lymph nodes metastasis (LNM), the extent of surgery was recommended as either lobectomy or total thyroidectomy (TT) [11], depending on the intentionality from patients and surgery team. However, some scholars argued that total thyroidectomy has the advantage of allowing individualized postoperative risk stratification and surveillance [12], and some other previous studies have reported that in patients with unilateral thyroid cancer who underwent total thyroidectomy, contralateral malignant tumors, defined as occult thyroid carcinoma, also represented a nonnegligible proportion [13][14][15][16][17]. Furthermore, evidence indicates that multifocality, including occult contralateral or bilateral thyroid cancer, is an independent risk predictor of recurrence after lobectomy [18].…”
Section: Introductionmentioning
confidence: 99%